Diversity Climate as a Multilevel Strategic Mechanism: A Bibliometric and Scoping Review of Three Decades of Global Research - Anindra Guspa; Wildan Haru Pradani (Universitas Muhammadiyah Surakarta, 2026)
Diversity climate refers to shared perceptions of how organizations and educational institutions value, support, and fairly manage differences related to ethnicity, gender, culture, and other social identities. This study aims to map the global development of diversity climate research and synthesize evidence on its roles and outcomes. Using a combined bibliometric and scoping review of 158 Scopus-indexed articles published between 1993 and 2025, publication trends, key themes, and empirical patterns were identified, with 45 studies included in the qualitative synthesis. The results show a strong growth of diversity climate research since the late 2000s, dominated by Western countries but increasingly expanding to other regions. The findings indicate that diversity climate functions as a multilevel mechanism influencing psychological well-being, team cohesion, innovation, employee retention, and students' intercultural development. Overall, diversity climate plays a strategic role in transforming diversity into inclusion, resilience, and performance in culturally diverse institutions.